Fabrication of Native and Enzymatically Modified Durian Seed (Durio zibethinus Murr.) Starch - Susi Afrianti Rahayu; Nasrul Wathoni; Sriwidodo Sriwidodo; Lisa Sophianingsih (Universitas Padjadjaran (Unpad), 2019)
Durian seed (Durio zibethinus Murr.) has a high starch content (46.2%) and thus can be used as a new source of starch for the raw materials of pharmaceutical and food industries. In this study, we fabricated native and enzymatically modified durian seed starch using a rough enzyme extract from Saccharomycopsis fibuligera. Wet grinding method was used for starch production. Physicochemical characterization of the starches was investigated by organoleptic, acidity-basicity, loss on drying, flow capability, compressibility, ash content and microbial limit. In addition, viscoamylograph had been done to clarify the viscosity properties of the starches. The result of starch production showed that the durian seed had a starch yield of 17.68%. Physicochemical characterization of the starch showed that the results of quality testing had fulfilled the Indonesian Pharmacopoeia 4th edition standards requirements, such as description, identification, acidity-basicity, loss on drying, ash content and microbial limit. In addition, viscoamylograph study showed that the enzymatically modified durian seed starch had a higher viscosity than the native durian seed starch. Interestingly, modification of the durian seed starch using a rough enzyme extract improved its flow capability and compressibility. These results suggest that the modified durian seed starch experienced an increase in viscosity, compressibility and flow capability compared to native durian starch. Keywords: durian, seed, starch, enzymatic modification